Angiotensin II receptor blockade alleviates calcineurin inhibitor nephrotoxicity by restoring cyclooxygenase 2 expression in kidney cortex. (18th January 2021) - Hu, Junda; Xu, Yan; Bachmann, Sebastian; Mutig, Kerim
Abstract: Aim: The use of calcineurin inhibitors such as cyclosporine A (CsA) for immunosuppression after solid organ transplantation is commonly limited by renal side effects. CsA‐induced deterioration of glomerular filtration rate and sodium retention may be related to juxtaglomerular dysregulation as a result of suppressed cyclooxygenase 2 (COX‐2) and stimulated renin biosynthesis. We tested whether CsA‐induced COX‐2 suppression is caused by hyperactive renin‐angiotensin system (RAS) and whether RAS inhibition may alleviate the related side effects. Methods: Rats received CsA, the RAS inhibitor candesartan, or the COX‐2 inhibitor celecoxib acutely (3 days) or chronically (3 weeks). Molecular pathways mediating effects of CsA and RAS on COX‐2 were studied in cultured macula densa cells. Results: Pharmacological or siRNA‐mediated calcineurin inhibition in cultured cells enhanced COX‐2 expression via p38 mitogen‐activated protein kinase and NF‐kB signalling, whereas angiotensin II abolished these effects. Acute and chronic CsA administration to rats led to RAS activation along with reduced cortical COX‐2 expression, creatinine clearance and fractional sodium excretion. Evaluation of major distal salt transporters, NKCC2 and NCC, showed increased levels of their activating phosphorylation upon CsA. Concomitant candesartan treatment blunted these effects acutely and completely normalized the COX‐2 expression and renal functional parameters at long term. Celecoxib prevented the candesartan‐induced improvements of creatinine clearance and sodium excretion. Conclusion: Suppression of juxtaglomerular COX‐2 upon CsA results from RAS activation, which overrides the cell‐autonomous, COX‐2‐stimulatory effects of calcineurin inhibition. Angiotensin II antagonism alleviates CsA nephrotoxicity via the COX‐2‐dependent normalization of creatinine clearance and sodium excretion.